Thermoelectric properties of Ca3Co4O9–Co3O4 composites. Issue 8 (September 2015) - Delorme, F.; Diaz-Chao, P.; Guilmeau, E.; Giovannelli, F.
Abstract: (1− x )Ca3 Co4 O9 / x Co3 O4 composites samples with x =0, 10, 20 and 50 vol% have been prepared by solid state reaction and sintered by spark plasma sintering. Their thermoelectric properties have been studied in the range 323–1000 K. No reaction occurs between Co3 O4 and Ca3 Co4 O9 particles during the high temperature treatment. The addition of Co3 O4 particles within a Ca3 Co4 O9 matrix strongly influences the thermoelectric properties. The powerfactor decreases as the Co3 O4 content increases. As the thermal conductivity increases, this leads to lower ZT values. These modifications of the thermoelectric properties are consistent with the compressive strain on Ca3 Co4 O9 originating from the mismatch of thermal expansion coefficients of Ca3 Co4 O9 and Co3 O4 .